Does the Conference of Disarmament Have a Future? - Meyer, Paul (Journal for peace and nuclear disarmament, 2021)
The Conference on Disarmament (CD) has been in a prolonged state of paralysis. Since its negotiation of the Comprehensive Test Ban Treaty (CTBT) in 1996, it has not produced any other agreement and has been unable even to agree on a Programme of Work. The dysfunction of the CD has been a product of its extreme version of the consensus rule for decision-making and a counter-productive dynamic among its 65 member states that privileges national preference over the collective good that compromise could yield. The bankruptcy of the CD erodes the credibility of the multilateral disarmament enterprise as does the complicity of its members in perpetuating a diplomatic charade. Moving its core issues out of the CD and into negotiating forums not vulnerable to a de facto "veto" provides an escape route for those states genuinely interested in making progress. Without the political will to engage in creative diplomacy to break out of the CD's straitjacket, the outlook for the future of the UN's "single multilateral disarmament negotiating forum" looks bleak.